Sparks of genius portraits of electrical engineering excellence - Nebeker, Frederik (Institute of electrical and electronics engineers, 1994)
Biographical text chronicles the ground-breaking technological contributions made by eight of this century's most direction-setting engineers. DLC: Electric engineers-Biography.